Executive Guidelines No. (17) of the year 2025 Concerning Certain Rules and Controls Necessary for Applying the Provisions of the Tax Facilitation Initiative Laws - Ministry of Finance (2025)
In light of the launch of the first package of the Tax Facilitation Initiative by the Ministry of Finance and the Egyptian Tax Authority, the initiative aims to strengthen the relationship between the Tax Authority and its stakeholders, foster a true partnership among the parties of the tax system, and enhance the Authority’s public image. To achieve these objectives, the initiative introduces a series of legislative and executive measures covering (income tax, sales tax, value-added tax, stamp duty, and the State’s financial resources development fee). It establishes clear standards to achieve justice and transparency while outlining the mechanisms required to resolve tax disputes according to simplified tax accounting mechanisms. Additionally, the initiative takes into account the lower-income groups, by streamlining the procedures of their dealings with the Egyptian Tax Authority and alleviating their tax burdens. These efforts aim to support and encourage taxpayers, ultimately enhancing compliance with tax laws and commitment to their integration into the formal economy.